Antagonism of vWF Inhibits both Injury Induced Arterial and Venous Thrombosis in the Hamster - Yamamoto, Hiroshi; Vreys, Ingrid; Stassen, Jean Marie; Yoshimoto, Ryota; Vermylen, Jos; Hoylaerts, Marc F. (Thrombosis and Haemostasis, 1998)
von Willebrand factor (vWF) is instrumental in arterial but has also been implicated in venous thrombogenesis. To address its role in venous thrombosis, experimental thrombosis was induced in the carotid artery and the femoral vein of hamsters, following which thrombus prevention by two different antagonists of vWF was studied. The first antagonist was the anti-human vWF monoclonal antibody AJvW-2, which inhibits the botrocetin and ristocetin induced aggregation of human blood platelets. AJvW-2 reacts with an epitope present in the A1 domain of vWF in very different species (human, pig, rabbit, dog, Guinea pig and rat). This epitope was found to be conformational and overlapping with vWF binding sites for aurin tricarboxylic acid (ATA), but not for botrocetin and heparin. AJvW-2 has affinities for vWF in the absence (Kd = 0.5 ± 0.03 nmol/l in solution) and in the presence of shear stress (Kd = 3.3 ± 0.6 nmol/l during perfusion at 1,300 s–1 over subendothelial matrix associated vWF) sufficiently elevated to neutralize vWF. During perfusion of subendothelial matrix with anticoagulated human blood, the surface covered by adhering platelets was reduced by AJvW-2, with IC50s equal to 6.6 ± 0.34 μg/ml at 1,300 s–1 and to 1 ± 0.01 μg/ml at 2,700 s-1. As a second antagonist, molecular size gel filtered ATA was selected. Fractionated ATA inhibited platelet adhesion to matrix with IC50s equal to 0.27 ± 0.09 mmol/l at 1,300 s –1 and 0.16 ± 0.008 mmol/l at 2,700 s –1. When administered to hamsters, AJvW-2 prevented thrombosis in the injured carotid artery dose-dependently (ED50 = 0.15 ± 0.01 mg/kg). Thrombosis in the similarly injured femoral vein was however also inhibited (ED50 = 0.37 ± 0.06 mg/kg). Likewise, fractionated ATA completely inhibited carotid artery thrombosis (ED50 = 0.42 ± 0.13 mg/kg), but also interfered with femoral vein thrombosis (apparent ED50 between 2 and 3 mg/kg). We conclude that antagonizing the vWF A1 domain by AJvW-2 and to a lesser extent also by fractionated ATA, inhibits thrombosis not only in the arterial but also in the venous circulation. Since venous thrombi were prevented at only 3-5-fold higher doses of antagonist, vWF participates in injury induced venous thrombosis.